Sociodemographic Characteristics as Determinants and Physical Performance Measures as Correlates of Falls Among Malaysian Community-Dwelling Older Adults - Singh, Devinder Kaur Ajit; Samah, Zunaidah Abu; Shahar, Suzana; Omar, Mohd Azahadi; Shaharudin, Muhammad Iqbal; Chin, Ai-Vyrn (Lippincott, Williams & Wilkins, 2019)
There is limited information regarding combined sociodemographic data and physical performance measures as determinants and correlates of falls among community-dwelling older adults. In this study, we aimed to identify whether sociodemographic data and physical performance measures are significant determinants and correlates for falls in community-dwelling older adults. Three hundred twenty-five Malaysian community-dwelling older adults (145 men and 180 women), aged 60 to 89 (M = 67.64, SD = 5.56) years, were recruited through multistage random samplings for this prospective study (with 6 months' follow-up). Binary logistic regression analysis was performed on the sociodemographic data and physical performance measures to determine the determinants and correlates of falls among these participants. The Physiological Profile Assessment (PPA) was the only significant (P <.05) physical performance measure that correlated with falls. The Timed Up and Go (TUG) Test and education levels were significant correlates and determinants of falls in this population, with the absence of PPA in the model. The PPA is the best physical performance measure correlate of falls among Malaysian community-dwelling older adults. However, when the PPA is not available, the TUG Test, although a simple performance tool, may be used to predict falls among community-dwelling older adults. © 2019 Wolters Kluwer Health, Inc. All rights reserved.